PKM STRATEGI PEMASARAN YANG DILAKUKAN DI PLAZA TUNJUNGAN III SURABAYA DALAM MEMASARKAN PRODUK - Eko Saputra (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
The conclusion of this research, consumers of Black Canyon Coffee restaurants are: (1) men who aged of 21-35 years; (2) consumers that obtain information from the friend by 47%, 37% are from the business relationship, 13% are from the family; (3) consumers desires to come again to the Black Canyon Coffee restaurant as much as 44% are said maybe, and 37% are said yes. The marketing strategy that undertaken by Black Canyon Coffee restaurant is to increasing presentation speed and food quality, increasing cleanliness of restaurant, hospitality and neatness of staffs’ appearance. The increasing of promotion both through of printing and electronic media, or by a billboard so that its presences are more to be known by the public.